PENINGKATAN KEMAMPUAN KOGNITIF MELALUI PERMAINAN RODA PUTAR PADA ANAK KELOMPOK A DI TKN PAKUNDEN 1 KOTA BLITAR - peni pratiwi (Jurnal Pendidikan : Riset dan Konseptual, 2019)
ABSTRACT: The main purpuse of this research is to describe the application of turning wheel game to improve kognitive skill of group A students at Pakunden 1 kindergarten Blitar town. This Classroom Action Research used 2 cycles. The result of this research showed that it can improve learning activity well. It could also increas students cognitive skill. The percentage result of cognitive skill in pre-test was 38,1%, in cycle I was 49,9%, and in cycle II was 89,5%